Ce que la peinture d’histoire fit à la nation britannique : l’invention picturale de la Grande-Bretagne (1688-1836) - Isabelle Baudino (Revue Française de Civilisation Britannique)
This article analyses both the theory and practise of history painting in Britain between 1688 and 1836. Through the outlining of three phases (appropriation, realisation and autonomisation) this study intends to explore the role of artistic theories and narrative pictorial practises in the construction of a national identity.